If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2 + 2m) = 10 + 2m (2 * 5 + 2m * 5) = 10 + 2m (10 + 10m) = 10 + 2m Add '-10' to each side of the equation. 10 + -10 + 10m = 10 + -10 + 2m Combine like terms: 10 + -10 = 0 0 + 10m = 10 + -10 + 2m 10m = 10 + -10 + 2m Combine like terms: 10 + -10 = 0 10m = 0 + 2m 10m = 2m Solving 10m = 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 10m + -2m = 2m + -2m Combine like terms: 10m + -2m = 8m 8m = 2m + -2m Combine like terms: 2m + -2m = 0 8m = 0 Divide each side by '8'. m = 0 Simplifying m = 0
| 9=6.5 | | 32p-2=-78 | | 2918+12x=-53x+13 | | 2(5f+5)= | | x-(x*.0765)=200 | | f(t)=-4t^2+16t+9 | | -3j-(-4)/-6-12 | | 3x+21=13x+59 | | -8+2m=-16.4 | | -4x=-250 | | x^2-16x+35=0 | | 2(6X)-4=32 | | 178-x=254 | | 17 = g3+ 13 | | 8x+36+5x+60= | | 2/7x=100 | | 2(-5-x)+6x-7=5 | | a+5=42*6 | | 9/11=-19/x | | 72x-78=30 | | 14=3+b+5 | | 5x=80+15 | | -1+8(x-2)=15x+3-7x | | 7x/x-60 | | 7x/x-69 | | -3-3(0)=0 | | 6(-2n+4)-2n=-6+3 | | 35+5a=10 | | (8-2x)/6=15 | | Y+(7y+21)=2Y+45 | | -3x^2-150=0 | | 6t-5=2t+9 |